(untitled) (PANGEEA, 2025)
The overall objective of the research was to study the modification of soil properties under the influence of agricultural practices, in relation to its permeability and water reserve formation. The research area was represented by the Vasluie watershed, where a pedological study was conducted to identify the soils in the area. Pedological research in the studied area was carried out using 25 main profiles, from which soil samples were taken, both in their natural state and modified, for physico-chemical analysis. The study was conducted in a three-year rotation with three types of crops: soybean, wheat, and corn. Each crop was placed in five soil management systems, and each system had five variants of mineral, organic, and crop residue fertilization. The following soil management systems were established: plowing at a depth of 20 cm, at 30 cm, plowing without turning the furrow with the chisel and the paraplow, and the one-year plowing and one-year disking variant